Pengaruh Media Video Pernikahan Usia Dini Terhadap Tingkat Pengetahuan Remaja Putri - Dianna, Dianna; Fitriani, Henny; Hidayati, Nur Kurnia (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Marriage that takes place in adolescence will generally cause problems both physiologically, psychologically and socio-economically. The impact of marriage at a young age is more evident in adolescent girls than in adolescent boys. Video media increases recall from 14% to 38%. So that it can increase knowledge. Knowing the Effect of Video Media on Early Marriage on the Knowledge of Adolescent Girls in the Tebas Health Center Working Area. Using the Quasi Experiment method, pre & post test approach without control group design. The sample of adolescent girls in Tebas Sungai Village, Tebas Health Center Working Area was 89 respondents with proportionate stratified random sampling technique. Wilcoxon statistical test. There is an effect of Video Media on Early Marriage on the Knowledge of Adolescent Girls in the Tebas Health Center Working Area with a p value of 0.000 <0.05. There is an effect of Video Media on Early Marriage on the Knowledge of Adolescent Girls in the Working Area of Puskesmas Tebas. Keywords: Knowledge, Video Media, Early Marriage  ABSTRAK Pernikahan yang terjadi pada usia remaja pada umumnya  menimbulkan permasalahan fisiologis, psikologis, dan sosial ekonomi.  Dampak pernikahan di usia muda lebih terasa pada remaja perempuan dibandingkan remaja laki-laki. Media Video meningkatkan ingatan dari 14% menjadi 38%. Sehingga dapat meningkatkan pengetahuan. Mengetahui Pengaruh Media Video Pernikahan Usia Dini Terhadap Tingkat Pengetahuan Remaja Putri Di Wilayah Kerja Puskesmas Tebas. menggunakan metode Quasi Experiment, pendekatan pre & post test without control group design. Sampel remaja putri di Desa Tebas Sungai Wilayah Kerja Puskesmas Tebas sebanyak 89 responden dengan tekhnik proportionate Stratified Random sampling. Uji statistik Wilcoxon. Terdapat pengaruh Media Video tentang Pernikahan Usia Dini terhadap Pengetahuan Remaja Putri di Wilayah Kerja Puskesmas Tebas dengan nilai p value 0,000 < 0,05. Terdapat pengaruh Media Video tentang Pernikahan Usia Dini terhadap Pengetahuan Remaja Putri di Wilayah Kerja Puskesmas Tebas. Kata Kunci: Pengetahuan, Media Video, Pernikahan Usia Dini